Intrauterine intestinal volvulus prompting emergency delivery and surgery in a 32wk fetus - Kamalesh Pal; Louay Hassan Zayed; YounisMohamed Morsy Khalid (Elsevier, 2020)
Fetal intestinal volvulus is a medical emergency with potentially fatal consequences thus requires a high index of suspicion and prompt intervention. Echogenic dilated bowels, Whirlpool/Coffee bean signs, polyhydramnios, fetal anemia, fetal ascites with aperistalsis, nonreaasuring CTG are few important diagnostic signs. Mostly it has been described without associated malrotation,as segmental volvulus due to malfixation of gut with or without associated anaomalies such as meconium ileus, CDH, abdominal wall defects. We describe for the first time a case of 1.9kg female fetus detected to have intestinal volvulus associated with multiple ileal atresias and mesenteric defect. The fetus had classical Whirlpool sign, polyhydramnios and anemia, was delivered by emergency Ceasarian Section, post natally detected to have tense abdomen, confirmed Whirlpool sign on post natal USG, underwent emergency laparotomy, resection of necrotic ileal loops & I-C junction and Jejuno-Colic anastomosis. Child adapted to elemental feeding with 50cm of Jejunum without Ileo-cecal valve without shortbowel syndrome. Importance of multidisciplinary perinatal care, possible intrauterine vascular accident in pathogenesis of atresia and fetal volvulus has been emphasized in the case report.